Canine Distemper Virus (CDV) Transit Through the Americas: Need to Assess the Impact of CDV Infection on Species Conservation (2023)
Canine Morbillivirus (also known as Canine Distemper Virus—CDV) is the causative agent of one of the most important diseases in domestic dogs and wild fauna. It belongs to the Paramyxoviridae family, orderMononegavirales, which has a non-segmented